2020
DOI: 10.1017/s0950268820001478
|View full text |Cite
|
Sign up to set email alerts
|

The descriptive epidemiology of coronavirus disease 2019 during the epidemic period in Lu'an, China: achieving limited community transmission using proactive response strategies

Abstract: Abstract Hubei province in China has had the most confirmed coronavirus disease 2019 (COVID-19) cases and has reported sustained transmission of the disease. Although Lu'an city is adjacent to Hubei province, its community transmission was blocked at the early stage, and the impact of the epidemic was limited. Therefore, we summarised the overall characteristics of the entire epidemic course in Lu'an to help cities with a few imported cases better contain the epidemic. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…In two studies, 9 40 summary statistics are provided and CIs were generated 32 reported a mean value for the serial interval using a regression model. In the study by Qin et al, 12 summary statistics and CIs are provided but the method used for obtaining the CIs is unclear. In the remaining six studies, 3 26-29 38 varying degrees of summary statistics such as the mean, median and quantiles are provided.…”
Section: Resultsmentioning
confidence: 99%
“…For three papers from which we were unable to extract either sufficient parameters to simulate distributions, or underlying serial interval data, 12 29 38 two 29 38 supplied histograms representing the serial interval data in their papers.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas many statistics are generated by the TFP Scanner and many variations of this analysis are possible depending on cluster thresholds, we systematically explored a wide range of statistics and thresholds as the basis for EWS leading indicators. The analysis included the calculation of logistic growth rates (LGRs) for clusters (monophyletic clades above a given size threshold) within each phylogeny using two different methods: (1) a generalised linear model (GLM) to calculate the log odds of a sample being from a cluster of interest compared to a geographically (by country) and temporally matched sample weighted by prevalence, and multiplied by the estimated mean generation time of 6.5 days 20 , 21 , 22 , 23 to calculate the relative LGR per generation for each cluster of interest (the method is not sensitive to the value selected for generation time, see Supplementary Material for details); and (2) a generalised additive model (GAM) combined with a Gaussian process model to identify changes in growth rates over time. A third growth rate output is computed for each cluster as being either (1) or (2) depending on the level of model support calculated using the Akaike Information Criterion (AIC) and ‘relative likelihood’.…”
Section: Methodsmentioning
confidence: 99%